2018
DOI: 10.1016/j.bbi.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Replication and reproducibility issues in the relationship between C-reactive protein and depression: A systematic review and focused meta-analysis

Abstract: One of the most common inflammatory markers examined in depression is C-reactive protein (CRP). However, the magnitude of the association between CRP and depression when controlling for potentially confounding factors such as age, sex, socio-economic status, body mass index, medication and other substance use, and medical illness, is unclear. Inconsistencies in other methodological practices, such as sample collection, assaying, and data cleaning and transformation, may contribute to variations in results. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 240 publications
(280 reference statements)
2
92
0
Order By: Relevance
“…In the largest study to date, we found hs-CRP was not associated with depression among generally healthy adults after controlling for BMI. Our findings are consistent with prior population-based studies that found no significant association between CRP and depression independent of BMI 12 15. Our findings also align with other studies that found no association between CRP and depression independent of other covariates related to depression, including antidepressant use and chronic illness 10 11 13 16 27…”
Section: Discussionsupporting
confidence: 92%
“…In the largest study to date, we found hs-CRP was not associated with depression among generally healthy adults after controlling for BMI. Our findings are consistent with prior population-based studies that found no significant association between CRP and depression independent of BMI 12 15. Our findings also align with other studies that found no association between CRP and depression independent of other covariates related to depression, including antidepressant use and chronic illness 10 11 13 16 27…”
Section: Discussionsupporting
confidence: 92%
“…First, we studied a well-powered, homogeneous sample of patients with MDD. Second, we investigated high-sensitivity CRP (hsCRP) levels, a serum marker that has frequently been shown to provide reliable assessments of peripheral inflammation in MDD 23 as well as in other psychiatric disorders, such as bipolar disorder 24 and psychosis, 25 and that has repeatedly been associated with brain structural alterations. 16,20,22,26 Third, we used a voxel-based morphometry approach, which does not rely on a priori selection of regions of interest, allowing us to investigate structural alterations across the entire brain.…”
Section: J Psychiatry Neurosci 2019;44(6)mentioning
confidence: 99%
“…In fact, elevated inflammation is associated with treatment-resistant depression (Yang et al, 2019). In particular, the acute phase reactant Creactive protein (CRP) arguably is the most researched inflammatory index in depression research (Horn et al, 2018;Howren et al, 2009). CRP is a non-specific pentameric protein synthesized in the liver that is upregulated during the acute phase of inflammation in response to stimulation from other proinflammatory proteins (e.g., interleukin (IL)-6 and IL-1 ; Du Clos, 2000).…”
Section: Introductionmentioning
confidence: 99%